KEBIJAKAN KLASTER INDUSTRI SEBAGAI STRATEGI PEMBANGUNAN EKONOMI WILAYAH - Mardiana, Mardiana; Tampubolon, Dahlan (Jurnal Kebijakan Publik, 2021)
The cluster policy is an option for regions to spur regional development. Encouraging strong local industry is an attractive view for actors as a way of concentrating economic activity in the region. If the cluster policy is successful, it can contribute to job creation and the initiation of growth processes in the region. This makes cluster policy an attractive tool for regional economic policy. This article presents a case study from Riau Province as well as some theoretical considerations on the use of cluster policies.The industrial cluster in Riau is mainly for processing agricultural products for export purposes, except for the one in Pelalawan Regency with its Techno Park. The other five industrial clusters still prioritize the food industry group and processed palm oil products. In cases such as Buruk Bakul in Bengkalis Regency and Kuala Enok in Indragiri Hilir Regency, other political instruments are more likely to be the method of choice. Reliable resources are available, reviving through new production centers. In some cases, the efforts of the cluster policy did not achieve the optimal goal. Apart from Kuala Enok and Buruk Bakul, the Techno Park area in Pelalawan Regency is also not optimal, while the Tenayan area in Pekanbaru City has no industry or tenants who rent it.